Genetic evaluation of F2 inbred strain of Swiss albino mice by microsatellite markers - KAUSHAL, SHOBHANA; KUMAR, PUSHPENDRA; KUMAR, AMIT; SAINI, B L; TARANG, MITEK; CHAUHAN, ANUJ; PRAKASH, JAI; BHUSHAN, BHARAT (The Indian Journal of Animal Sciences, 2021)
Genetic characterization of F2 inbred Swiss albino mice was done using 11 microsatellites markers (D1Mit15, D2Mit51, D2Mit61, D3Mit15, D3Mit55, D5Mit18, D7Mit323, D8Mit14, D9Mit27, D10Mit180, and D11Mit167). The results indicated that genotypic frequencies at all the loci were in Hardy-Weinberg disequilibrium (P<0.001). Total number of alleles per locus ranged from 3 (D2Mit61, D3Mit15, D8Mit14, D9Mit27, D10Mit180, D11Mit167) to 4 (D1Mit15, D2Mit51, D3Mit55, D5Mit18, D7Mit323), with a mean of 3.45. The numbers of effective alleles ranged between 1.847 and 3.814. The observed heterozygosity (Ho) was maximum for D1Mit15 (0.660) and minimum for D5Mit18 (0.080), with mean of 0.269. The FIS estimates was ranged from 0.0817 (D1Mit15) to 0.8799 (D5Mit18). The average inbreeding coefficient was 0.592, which indicates that parents were more related than expected under random mating. The range of PIC value (from 0.414 to 0.689) for various microsatellite loci was revealing that population under investigation was of high diversity maintaining a multiple allele.